No News From Geneva: The Changing Relationship of Regional Trade Agreements and the WTO - Alschner, Wolfgang (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2025)
In an article entitled “News from Geneva on RTAs and WTO-plus, WTO-More, and WTO-Minus”, published in 2009, Gabrielle Marceau analyzed the jurisdictional conflicts between Regional Trade Agreements (RTAs) and the World Trade Organization (WTO), introducing the now classic WTO-plus, WTO-more, and WTO-minus typology. At the time, she feared that the multiplication of RTAs, with their own rules and dispute settlement mechanisms, could undermine coherence and crowd out multilateral rulemaking, though she also noted their potential to serve as laboratories for future multilateralization. Today, however, in the context of a weakened WTO—paralyzed in its dispute settlement and sidelined in negotiations—RTAs function more as a safety net, replicating and reinforcing multilateral rules. The article revisits the three categories: WTO-plus provisions deepen liberalization and align with WTO goals, though they may duplicate or decentralize obligations; WTO-more provisions broaden trade agreements to cover social, environmental, and sustainability concerns, which have now moved from the margins to the core of trade policy; and WTO-minus provisions restrict existing WTO rights or obligations, posing risks to developing countries and representing an existential threat to multilateralism. The overall argument is that while the WTO’s centrality has eroded, RTAs can either stabilize and renew the global trade order through WTO-plus and WTO-more provisions or fragment it further if WTO-minus trends prevail.